Besitzwechsel und sozialer Wandel Lebensläufe und sozioökonomische Entwicklungen im südlichen Böhmerwald, 1640-1840 - Zeitlhofer, Hermann (2014)
This book deals with the changing patterns of transmission of land and houses in a pre-industrial rural community of Southern Bohemia. By linking different sources, such as land registers and a family reconstitution, the study focuses on both the demographic and the economic factors that influenced peasant transmission strategies as well as on the consequences of changing transmission patterns for access to land-ownership.